Complementary assets, patent thickets and hold-up threats: Do transaction costs undermine investments in innovation? - Franz Schwiebacher (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
Innovation is commercialization of technology. Imperfections in markets for technology should leave marks on physical investments for innovation. Two types of transaction costs could affect innovative investments: royality stacking and hold-up threats. Backward references in firm's patent portfolio indicate potential technology suppliers. I find a negative effect of ownership fragmentation on investments related to innovation for firms with small patent portfolios. Hold-up threats are credible when upstream patentees have less specific capital sunk than innovating firms. Differences in fixed capital stocks between downstream firms and upstream patentees negatively affect investments in innovation for firms with large patent portfolios. These effects are specific to investments in innovation. There are no comparable effects on investments in R&D or residual physical investments. The effects of patent thickets on innovation are thus not uniform. They depend on the characteristics of the downstream firm.
Keywords: O31; O34; 330; Market for Technology; Complementary Assets; Transaction Costs; Patent Thickets